Dosis de gallinaza y su efecto en el rendimiento agronómico del sacha trigo fundo Zungarococha 2021 - Sanchez Sandi, Josep Manuel (2025)
The work was carried out in the Agrostological Workshop, the purpose was to evaluate the optimal dose of chicken manure and the benefit in the agronomic production of Coix lacrima.jovi, evaluated at the 9th week, the study was quantitative, experimental, the population universe consisted of 480 bushes of the species, distributed in 12 beds with 40 species each and a distance between plants and rows of 0.50 x 0.50 m, for evaluation random sampling was considered, taking 4 plants per treatment, it is also worth stating that for each planting hole 8 botanical seeds were deposited, finished the evaluations of the variables studied it is concluded: That the organic fertilizer affects the agronomic characteristics of the forage species and that the best procedure was presented by T3 (4 kg of chicken manure / m2) with averages of: Plant height (1.60 cm), Biomass (6,400 kg / m2), dry matter (1.33 kg/m2) and yield per hectare (64 T/ha), the hypothesis is accepted, and it is recommended to carry out work on this species with other types of organic fertilizers, planting density, and number of seeds per planting.